Behavioral Changes Under Levetiracetam Treatment in Dogs - Erath, Johannes Roland; Nessler, Jasmin Nicole; Riese, Franziska; Hünerfauth, Enrice; Rohn, Karl; Tipold, Andrea (Frontiers in Veterinary Science, 2020)
In veterinary medicine levetiracetam (LEV) is a well-tolerated antiepileptic drug (AED) with only mild to moderate side effects. Behavioral changes are rarely reported in animals. In contrast, in human medicine the impact of LEV on behavior has frequently been described. Since in the Clinic for Small Animals at the University of Veterinary Medicine Hannover single canine patients were observed with behavioral abnormalities after LEV treatment, it was hypothesized that levetiracetam induces behavioral changes or causes an intensifying of pre-existing behavioral abnormalities in dogs with epileptic seizures. This monocentric retrospective study evaluated the incidence of behavioral changes in epileptic dogs treated with the antiepileptic drug LEV based on information obtained in a questionnaire completed by dog owners. Eighty-four client-owned dogs with recurrent seizures receiving LEV as monotherapy, add on treatment or pulse therapy met inclusion criteria. Approximately half of the dogs in the study population were reported to have preexisting behavioral changes before treatment with LEV, and some of these dogs were reported to experience a worsening of behavioral changes (14/44) or the emergence of new behaviors after initiation of LEV therapy (4/44). One quarter of the dogs without pre-existing behavioral abnormalities developed behavioral changes associated with the administration of LEV (10/40). Based on these results, the authors conclude that behavioral changes can occur in dogs being administered LEV, and this should be taken into consideration when discussing treatment options with owners.